Integrasi Nilai-Nilai Salafiyah dan Kewirausahaan Modern di Pondok Pesantren Wirausaha Kebon Cinta - Munjiat, Siti Maryam; Umihani, Umihani; Nuryadien, Mahbub (INCARE, International Journal of Educational Resources, 2024)
This study explores the entrepreneurship education model and its teaching strategies implemented at the Kebon Cinta Entrepreneurial Islamic Boarding School. The research is a type of field study using a qualitative approach with a naturalistic or interpretive paradigm. Data were collected from a natural setting as the primary source. Data analysis was conducted through techniques such as data reduction, coding, and categorization to identify key patterns in the findings. This process was followed by a category examination to gain a deeper understanding. The findings of this research are as follows: (1) The entrepreneurial values instilled at the Kebon Cinta Islamic Boarding School are worship-based entrepreneurial principles, where all economic activities are carried out with the intention of worshiping Allah SWT; (2) The entrepreneurship education process involves training students (santri) to manage economic institutions within the boarding school under the supervision and guidance of the kyai and the boarding school administrators.